Dark personality traits and cyber-dating abuse: The moderating role of empathy: Dark personality traits and cyber-dating abuse: The moderating role of empathy (Archives of Criminology, 2025)
The results of research on cyber-dating abuse in intimate relationships are presented in this article. The study analysed dark personality traits (i.e. narcissism, Machiavellianism, psychopathy and sadism) treated as relevant individual risk factors for this kind of violence. The sample consisted of 200 young adults (72% women). The following measures were used in the research: the Cyber Dating Abuse Questionnaire, the Short Dark Tetrad and the Interpersonal Reactivity Index. The results indicate that the severity of both the Dark Triad and sadism is related to the perpetration of cyber-violence and victimisation from an intimate partner. The research also showed that men more often than women use direct aggression in cyber-dating abuse. Moreover, the moderating role of empathy in the relationship between dark personality traits and cyber-dating abuse was confirmed.